Enrichment procedures for isolating salmonellae from raw meat and poultry. - Thomason, B M (1978)
The combined use of direct enrichment in tetrathionate broth containing brilliant green dye and preenrichment in buffered peptone-water followed by enrichment in tetrathionate broth yielded the maximal recovery of salmonellae from raw meat and poultry samples.